18F-SynVesT-1 PET in Focal Cortical Dysplasia Type II With Thickening Cortex. (5th August 2022) - Tang, Yongxiang; Yu, Jie; Zhou, Ming; Chen, Chen; Hu, Shuo
Abstract: A case of 2-year-old girl with intractable seizures underwent 18 F-FDG PET and MRI for seizure focus localization. MRI demonstrated cortical thickening and blurring of the gray-white matter interface in the right postcentral gyrus with focal hypometabolism in 18 F-FDG PET. The patient subsequently was enrolled in clinical trial of 18 F-SynVesT-1 PET study in epilepsy; a more restricted area of reduced 18 F-SynVesT-1 uptake was noted in the thickened postcentral gyrus. The surgical limits of resection were defined based on ictal semiology, electroencephalography, and imagings. The patient is seizure-free after epilepsy surgery, with histopathology of focal cortical dysplasia type IIb.